Jewel beetles (Coleoptera, Buprestidae) of Zhetysu Alatau (Kazakhstan) - Aizhan M. Tleppaeva (Acta Biologica Sibirica, 2023)
Fifty-seven species and subspecies of jewel beetles (Buprestidae) from 20 genera, 11 tribes and 5 subfamilies (Julodinae, Polycestinae, Chrysochroinae, Buprestinae and Agrilinae) are recorded from Zhetysu (Dzhungar) Alatau Range. By species diversity at the subfamily level, the jewel beetles are distributed as follows: Julodinae – 1 species, Polycestinae – 5 species, Chrysochroinae - 14 species, Buprestinae – 14 species, Agrilinae – 22 species. At the genus level, Agrilus (15 species), Sphenoptera (9), Acmaeoderella (5), Anthaxia (5) and Chrysobothris (3) are the most abundant in the Zhetysu Alatau. The identified species of jewel beetles are confined to seven altitude belts and biotopes: the most populated is a shrub-steppe belt (25 species) followed by mountain-floodplain forests (14) and leaf-fir-forest belt (14), semidesert (11) and coniferous-forest (9) belts; medium-mountain mixedgrass belt (5) and subalpine meadows (2) demonstrate much poorer jewel beetle composition. Species of jewel beetles with known host plants are associated with arboreal and shrub plants from 21 families.